Myocardial infarction with non-obstructive coronary arteries (MINOCA): Intracoronary imaging-based diagnosis and management. Issue 5 (May 2021) - Sucato, Vincenzo; Testa, Gabriella; Puglisi, Sebastiano; Evola, Salvatore; Galassi, Alfredo Ruggero; Novo, Giuseppina
Highlights: The term MINOCA (myocardial infarction with non-obstructive coronary arteries) defines acute myocardial infarction with angiographic evidence of no significant coronary artery stenosis. Diagnosis may require multiple diagnostic tools, including intravascular ultrasound and optical coherence tomography. Abstract: Myocardial infarction with non-obstructive coronary arteries (MINOCA) is defined by clinical evidence of myocardial infarction (MI) with normal or near-normal coronary arteries on angiography. This condition is present in about 5% to 25% of patients presenting with acute coronary syndromes. MINOCA is a working diagnosis. Current guidelines and consensus recommend identification of underlying causes of MINOCA in order to optimize treatment, improve prognosis, and promote prevention of recurrent myocardial infarction. An accurate evaluation of patient history, symptoms and use of invasive and non-invasive imaging should lead to identification of epicardial or microvascular causes of MINOCA and differentiation from non-ischemic myocardial injury due to both cardiac (e.g. myocarditis) and non-cardiac disease (e.g. pulmonary embolism). In this review, we highlight the role of coronary imaging in differential diagnosis of patients presenting with MINOCA. Intravascular ultrasound and optical coherence tomography are well known technologies used in different settings from acute to chronic coronary syndromes. In MINOCA patients, coronary imaging could help to identify pathological alterations of the epicardial vessels that are not visible by coronary angiography such as plaque disruption, coronary dissection, coronary thromboembolism, coronary spasm, and coronary artery disease in patients presenting with takotsubo syndrome. In future, the widespread use of these technologies, in the right clinical context, could lead to optimization and personalization of treatment, and to better prognosis of patients presenting with MINOCA.